Assessing Self-Confidence Levels in EFL Students’ Speaking Performance - Fitrah, Atiyah Inayah; Korompot, Chairil Anwar; Sakkir, Geminastiti; Fauzan, Muhammad Miftah (Celebes Journal of Language Studies, 2024)
This study aims to assess the self-confidence levels of English as a Foreign Language (EFL) students in terms of their speaking performance. This study uses a quantitative approach with a quantitative descriptive method. The sample of the study consists of twenty-eight EFL students from the English Language Education study program, at Universitas Negeri Makassar using cluster random sampling. The data collection technique used a questionnaire as an instrument. The data were analyzed using SPSS 25 to find out the frequency and percentage distributions and to identify common patterns in self-confidence levels. Additionally, the mean score is calculated to provide a quantitative measure of the overall self-confidence among the respondents. The findings of the data analysis revealed that the level of EFL students’ self-confidence in speaking performance is at a high enough level with a score of 76.51. As a result, this study highlights the importance of self-confidence issues in EFL teaching practices and suggests that fostering a supportive learning environment could enhance students’ speaking performance and overall language proficiency.